2021
DOI: 10.3390/su13168846
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Scheduling of Hydro–Thermal–Wind–Photovoltaic Generation Using Lightning Attachment Procedure Optimizer

Abstract: This paper presents an effective solution for the short-term hydrothermal generation scheduling (STHS) problem using an integration of wind and photovoltaic power (PV) system. Wind and PV power are integrated into the power system to minimize the total fuel cost of thermal units. In this paper, the lightning attachment procedure optimization algorithm (LAPO) is employed to solve the STHS problem using the wind and PV power integration system. The proposed method is applied for solving five test systems with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In the past decades, combining HEPs and TPPs has been widely applied for short-term hydrothermal power systems [ 7 ]. Then, those such problems have been expanded by integrating RPPs into hydrothermal power systems such as short-term fixed head wind-hydro-thermal power systems [ 8 ], short-term variable head wind-hydro-thermal power systems [ 9 ], and solar-wind-hydrothermal power system [ 10 ]. The latter problems have the same feature as considering sufficient water in reservoirs for one day or one week, but this assumption is not valid for several dry seasons.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, combining HEPs and TPPs has been widely applied for short-term hydrothermal power systems [ 7 ]. Then, those such problems have been expanded by integrating RPPs into hydrothermal power systems such as short-term fixed head wind-hydro-thermal power systems [ 8 ], short-term variable head wind-hydro-thermal power systems [ 9 ], and solar-wind-hydrothermal power system [ 10 ]. The latter problems have the same feature as considering sufficient water in reservoirs for one day or one week, but this assumption is not valid for several dry seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Mohamed et al 36 considered LAPO for minimizing cost and emission of HTS and renewable energy based scheduling problems. The authors of Reference 36 showed usefulness of RESs (i.e., wind and solar) in traditional HTS by minimizing generation cost and emission using LAPO technique.…”
Section: Introductionmentioning
confidence: 99%
“…Mohamed et al 36 considered LAPO for minimizing cost and emission of HTS and renewable energy based scheduling problems. The authors of Reference 36 showed usefulness of RESs (i.e., wind and solar) in traditional HTS by minimizing generation cost and emission using LAPO technique. Mohamed et al 37 introduced grey wolf optimizer and cuckoo search based hybrid algorithm and showed the performance of the hybrid algorithm by minimizing generation cost and emission of the traditional and solar–wind integrated HTS problems.…”
Section: Introductionmentioning
confidence: 99%